Pencapaian Student Wellbeing pada Kurikulum Merdeka: Studi di Kelas IV SD Negeri 39 Pontianak Kota - Riennova Riennova; Asrori Asrori; Siti Halijah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The realization of Student Wellbeing in schools is one of the important programs in improving the quality of education. Various efforts have been made by the government, one of which is the implementation of the Independent Curriculum as stated in the Decree of the Ministry of Education and Culture and Technology No. 56 of 2022. This research was conducted at SD Negeri 39 Pontianak Kota with the aim of describing efforts to realize Student Wellbeing in the Independent Curriculum. Research methods applied descriptive qualitative, data collection techniques through observation, interviews and documentation. The results showed the effectiveness of efforts to realize Student Wellbeing in the Merdeka curriculum to improve the quality of education by collaborating with various parties such as teachers and students. This study describes Student Well-Being according to grade IV students at SD Negeri 39 Pontianak Kota. According to grade IV students at SD Negeri 39 Pontianak Kota, Student Wellbeing is very important because it makes it comfortable during the learning process. Thus, the results of this study can be used as positive recommendations for the realization of Student Wellbeing in the Independent Curriculum in schools.